Zoonotic pathogens in the food chain - Hendrick, Stephen; Krause, Denis O. (CABI, 2010)
Examining the development, spread and transmission of zoonotic diseases through the food chain; from animals, through production processes to humans, this book discusses the ways modern food production systems contribute to the risk of zoonotic disease,and where mitigation strategies need to be focused. Covering factorsin the animal production process and attributes of microorganisms that allow potential contamination of food sources, this book discusses pathogens that have recently emerged as important infections, and new trends in animal production such as organic livestock farming and raw ..